BRAND IMAGE, PRODUCT QUALITY, AND CUSTOMER PERCEIVED VALUE TO INCREASE CONSUMER SATISFACTION AT THE BO5 PERFUME GROCERY STORE - Mufarokhah, Nur; Khasanah, Uswatun; Aji, Susilo (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2024)
This study aims to see the influence of brand image, product quality, and customer perceived of value in increasing Consumer Satisfaction. Sampling uses Proportional Stratified Random Sampling. The sample taken used as many as 100 respondents who had bought products at the BO5 Perfume Gresik Shop more than once. The method used in this study uses a quantitative method. The type of data used is primary data. The data collection method uses a questionnaire and is processed using the SmartPLS 4 analysis tool. The data analysis technique uses SEM (Structural Equation Modeling). The results of this study show that Brand Image has a positive and significant effect on Consumer Satisfaction, Product Quality has a negative and insignificant effect on Consumer Satisfaction, Customer Perceived Value has a positive and significant effect on Consumer Satisfaction. This research is intended to provide suggestions and input to the BO5 Perfume Gresik Shop in order to increase Satisfaction and Loyalty in consumers.